Childhoods in Policy: A Critical Analysis of National Child Protection Policy in the Philippines. (14th October 2018) - Roche, Steven
Abstract : This article investigates policy in the Philippines relating to the protection of children, which, despite policy efforts in this space, and growing evidence of child maltreatment and its impact, remains unexamined by the literature. It examines constructions of childhoods utilising a critical policy analysis of national policy documents concerning children's welfare and protection. Analysis finds conflicting representations of children's agency, defining children as 'becomings', but also as rights holders and social actors, viewing children as both embedded in, and reliant on, family, consequently detailing important insights into Filipino policy‐making and society.